Leituras do espaço na narrativa Espaço Terrestre, de Gilvan Lemos. - Ferraz, Rinalda Cordeiro Siqueira Costa (2022)
This study aims to examine links between concepts of space in Geography and Literature, taking as a source of research Espaço Terrestre, by Gilvan Lemos. It also seeks to investigate the imbrications of spatial geographic aspects and the space category in the featured narrative; to analyze the composition, both physical and idiosyncratic, of characters from the space category, in addition to verifying the interference of geographic space in the construction of changes in social behavior. In order to enable the development of this work, a bibliographic review was elaborated, composed by the readings of studies developed about the space category made by the geographers Yi Fu Tuan and Milton Santos, as well as the philosopher Henri Lefebvre. In the literary and linguistic field, great contributions were given by Osman Lins, Antônio Dimas and Mikhail Bakhtin. From this perspective, we believe that knowledge of the concept of geographic space can enhance the understanding of the Espaço Terrestre narrative. In this way, the analyses carried out in the work of Gilvan Lemos allowed us to point out that the perceptions and contributions brought by Geography to the study of literary space expand not only the vision of space from the fictional perspective but also of the author subject and the reader subject, through different fields of observation, reading and interpretation of space, which we characterize as stereoscopic from an interdisciplinary perspective.